1999
DOI: 10.1021/op9800663
|View full text |Cite
|
Sign up to set email alerts
|

The Bicyclo[3.2.0]heptan-endo-2-ol and Bicyclo[3.2.0]hept-3-en-6-one Approaches in the Synthesis of Grandisol:  The Evolution of an Idea and Efforts to Improve Versatility and Practicality

Abstract: In this paper we will disclose a chemistry story that started with a single molecule, the monoterpene grandisol, used in protecting cotton crops from an important pest, Anthonomus grandis Boheman. Initially, efforts were aimed at giving ever more practicality, versatility, and efficiency to a synthetic scheme that was centered on the key role of the 2,5-dimethylbicyclo[3.2.0]heptan-endo-2-ol, available from intermolecular photocyclization and methylation or, better and more conveniently, by an intramolecular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
0
4
0
2
Order By: Relevance
“…Oxygen substituents and, in particular, a hydroxy group can be positioned axially because this position facilitates additional binding to copper. 89 In the context of a synthetic approach to pseudolaric acid, Paquette and Pettigrew examined the [2 + 2] photocycloaddition of substrates rac - 19 and rac - 20 , which were submitted to the Cu(I)-catalyzed photocycloaddition as a mixture of diastereoisomers ( Scheme 8 ). 90 The resulting product mixture revealed that diastereoisomeric products rac - 23 were formed via a copper complex rac - 21 , in which the methyl group is equatorially and the hydroxy group is axially positioned.…”
Section: Cu(i) Catalysismentioning
confidence: 99%
“…Oxygen substituents and, in particular, a hydroxy group can be positioned axially because this position facilitates additional binding to copper. 89 In the context of a synthetic approach to pseudolaric acid, Paquette and Pettigrew examined the [2 + 2] photocycloaddition of substrates rac - 19 and rac - 20 , which were submitted to the Cu(I)-catalyzed photocycloaddition as a mixture of diastereoisomers ( Scheme 8 ). 90 The resulting product mixture revealed that diastereoisomeric products rac - 23 were formed via a copper complex rac - 21 , in which the methyl group is equatorially and the hydroxy group is axially positioned.…”
Section: Cu(i) Catalysismentioning
confidence: 99%
“…Die Synthese der in Abbildung 8 gezeigten Hydroazulensesquiterpene (+)-Aphanamol I (264) und II (265) wurde so über eine [2+2]-Photocycloaddition/Fragmentierung möglich. [340] Die Radikalfragmentierung von Verbindungen des Typs III wurde von Lange et al erfolgreich in Naturstoffsynthesen eingesetzt.…”
Section: Sesquiterpens (Ae )-B-himachalen (263) (Abbildung 8)unclassified
“…Diazotization of 3a with the safe and very convenient 2‐azido‐1‐ethylpyridinium tetrafluoroborate18 (generated in situ) afforded the expected α‐diazo‐β‐ketosulfone 3b as an oil, in practically quantitative yield. Reflux of a dichloromethane solution of the crude diazo compound 3b with a catalytic amount of rhodium acetate led to a smooth intramolecular carbenoid cyclization,19 to afford crystalline 1‐methyl‐4‐(phenylsulfonyl)bicyclo[3.2.0]heptan‐3‐one ( 4 )20 in 79% overall yield from 3a (Scheme ).…”
Section: Resultsmentioning
confidence: 99%